Characterization, Pathogenicity, and In Vitro Sensitivity of Rhizoctonia spp. Associated with Leaf and Sheath Spot of Bermudagrass Putting Greens in North Carolina and Alabama. Issue 1 (19th October 2017) - Kerns, James; Yan, Yan; Butler, Ernest
Abstract : Twenty isolates of a fungus resembling Rhizoctonia zeae were obtained from three golf courses with bermudagrass [ Cynodon dactylon (L.) Pers.] greens that were exhibiting leaf and sheath spot symptoms in 2013 and 2014. Morphological and molecular identification showed that 17 isolates were identified as R. zeae and three were identified as Waitea circinata var. zeae . Pathogenicity of the 20 isolates was determined by inoculating hybrid bermudagrass ('Champion') plants in a growth chamber. After inoculation, plants were incubated in a growth chamber at 34/30°C (day/night) and sealed in a closed container to ensure 100% humidity. After 7 d, disease was visually estimated using a modified Horsfall‐Barrett scale (0–10). All isolates were pathogenic to the hybrid bermudagrass cultivar Champion and aggressiveness among isolates varied. Sensitivity of seven isolates collected in 2013 to 16 fungicides (flutolanil, pyraclostrobin, fluoxastrobin, azoxystrobin, propiconazole, triticonazole, triadimefon, penthiopyrad, fluxapyroxad, azoxystrobin + difenoconazole, tebuconazole, difenoconazole, iprodione, polyoxin‐D zinc salt, fluxapyroxad + pyraclostrobin, and chlorothalonil) was tested. The sensitivity of 13 isolates collected in 2014 to five fungicides (chlorothalonil, azoxystrobin, pyraclostrobin, difenoconazole, and flutolanil) was tested. In general, all the isolates were extremely sensitive to demtheylation and succinate dehydrogenase inhibitor fungicides (50% effective concentration [EC50 ] < 1 mg a.i. L −1 ) and all isolates showed insensitivity to quinone outside inhibitor fungicides (EC50 > 10 mg a.i. L −1 ). These results demonstrated that R. zeae is a pathogen of ultradwarf bermudagrass under the imposed environmental conditions. Rhizoctonia zeae is sensitive to many fungicides, but based on in vitro sensitivity data presented here, some may not perform well under field conditions.